2010
DOI: 10.1038/ng.556
|View full text |Cite
|
Sign up to set email alerts
|

Subtle variations in Pten dose determine cancer susceptibility

Abstract: Cancer susceptibility has been attributed to at least one heterozygous genetic alteration in a tumor suppressor gene (TSG)1. It has been hypothesized that subtle variations in TSG expression can promote cancer development2,3. However, this hypothesis has not yet been definitively supported in vivo. PTEN is a TSG frequently lost in human cancer and mutated in inherited cancer-predisposition syndromes4. Here, we analyze Pten hypermorphic mice (Ptenhy/+), expressing 80% normal levels of Pten. Ptenhy/+ mice develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
451
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(481 citation statements)
references
References 21 publications
(33 reference statements)
24
451
0
6
Order By: Relevance
“…A similar role was attributed to PTEN in other types of cancers. 9 Subsequently, we explored the effect of siRNA PTEN silencing on KIT downstream signaling in vitro using GIST cell lines. Noteworthy, in both imatinib-sensitive and imatinib-resistant GIST cells, PTEN silencing resulted in overactivation of both, AKT and MAPK; the latter being exceptionally hyper-phosphorylated in imatinib-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar role was attributed to PTEN in other types of cancers. 9 Subsequently, we explored the effect of siRNA PTEN silencing on KIT downstream signaling in vitro using GIST cell lines. Noteworthy, in both imatinib-sensitive and imatinib-resistant GIST cells, PTEN silencing resulted in overactivation of both, AKT and MAPK; the latter being exceptionally hyper-phosphorylated in imatinib-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 In human malignancies, PTEN inactivation or insufficiency constitutively activates this pathway. 9 Thereby, GIST patients with PTEN deficiency could benefit from alternative therapies targeting the PI3K/AKT/mTOR pathway. In line with this concept, an oral mTOR inhibitor everolimus (RAD001, Novartis Pharmaceuticals) has been tested in combination with imatinib in phase I-II clinical trials for patients with imatinib-resistant GIST, pointing to a potential therapeutic benefit of the combined administration.…”
mentioning
confidence: 99%
“…PTEN was chosen as a candidate because (i) it is a shared target of miR-19 and miR-20a; (ii) small modifications of PTEN expression have important functional consequences (Alimonti et al, 2010), suggesting that deregulation of the micro-RNA level of regulation could be sufficient for a role in CoGAM induction and (iii) PTEN overexpression is known to inhibit growth of MCF-7 cells through induction of a G1 arrest (Weng et al, 1999). Clearly, complementation of Drosha knockdown by PTEN knockdown is only partial, and less efficient than miR-19 or miR-20 complementation.…”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72] With regard to SDH-related oncogenesis, it has been suggested that the tumor phenotypes could be affected by the size of SDH deletions because they can encompass closely located TSGs and compromise their function, which could lead to unusual phenotypes. 73,74 In addition, some research suggests that germ-line and somatic interactions could account for the clinical variability observed among carriers of an identical SDH germ-line mutation, including those within the same family.…”
Section: Mechanisms Of Biallelic Inactivationmentioning
confidence: 99%